Doubts, Problems and Certainties About Acute Appendicitis 2022
DOI: 10.5772/intechopen.95870
|View full text |Cite
|
Sign up to set email alerts
|

Acute Appendicitis: After Correct Diagnosis Conservative Treatment or Surgery?

Abstract: Acute appendicitis is the most common surgical disease presented in ED. Ongoing evidence in the literature, in the last 20 years, shows a lot of benefits in favor of conservative treatment. Despite that conservative treatment does not gain the correct position at the daily practice up to day. A large number of parameters related to acute appendicitis, present diversity in their appearance, so the final estimation of the disease may by unclear and the decision for treatment may be incorrect. We analyze these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…14 Similar results were seen in another study. 15,16 In a local study conducted by Safirullah et al conducted at Hayatabad Medical Complex and Lady Reading Hospital, Peshawar, concluded that appendicular mass can be successfully managed with conservative management. 17 In our study, the recurrence of acute appendicitis was seen in 6 (13.33%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similar results were seen in another study. 15,16 In a local study conducted by Safirullah et al conducted at Hayatabad Medical Complex and Lady Reading Hospital, Peshawar, concluded that appendicular mass can be successfully managed with conservative management. 17 In our study, the recurrence of acute appendicitis was seen in 6 (13.33%) patients.…”
Section: Discussionmentioning
confidence: 99%